(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The article presents data on the peculiarities of changes in the indicators of the circulatory and external respiratory systems of the body of Greco-Roman wrestlers aged 15-17 years in the preparatory period of the annual macrocycle when using a typical program for building a training process for the stage of specialized basic training in the process of training sessions. To implement the goal and objectives of the study, at the beginning and end of the training period, using traditional physiological methods and a computer program for express assessment of the functional state of the cardiorespiratory system "ShVSM-integral", testing of the current state of the cardiovascular system and external respiratory system of wrestlers who participated in the pedagogical experiment was carried out, with the determination of the main parameters of these systems, which characterize the energy capabilities of the heart and the features of the regulation of cardiac activity, the state of peripheral circulation, the efficiency of the circulatory system and its adaptive capabilities, the potential capabilities of the external respiratory system, the body’s resistance to hypoxia conditions and the general current state of the cardiovascular and respiratory systems of the body. The results of the study allowed us to ascertain certain positive changes in the functional state of the cardiorespiratory system of the examined wrestlers aged 15-17 years under the influence of a typical training process construction program: a significant decrease in the level of functional tension of the regulatory mechanisms of the cardiovascular system by 12.5%, an increase in the body’s resistance to hypoxia conditions by 11%, an increase in the level of the functional state of the cardiovascular system and the external respiratory system by 5%. At the same time, changes in other indicators of the functional state of the cardiorespiratory system were insignificant, statistically insignificant and had only a tendency to improve. In general, the results of the study allowed, firstly, to state the insufficient effectiveness of the typical program for building a training process for Greco-Roman wrestlers aged 15-17 in the preparatory period of the annual macrocycle and the need for its significant improvement, taking into account the existing world experience in training highly qualified wrestlers, and, secondly, the informativeness of the indicators of the cardiorespiratory system when assessing the current level of preparedness of Greco-Roman wrestlers.